Improving Student Motivation and Learning Outcomes Through Inquiry Learning - Leif, Forsblom; Steven, Gooding; Carol, Tuomi (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
School is basically a place where the teaching and learning process takes place between teachers and students. The students at school are always filled with the learning process from morning until going home at noon which makes the students' learning motivation decrease. Increasing student motivation in learning can be done through inquiry learning at school. This study was conducted to find out how the increase in motivation and learning outcomes of students studied through inquiry learning. In this regard, this research is a quantitative research by collecting data through surveys and in-depth interviews, the survey tool used by researchers is google form. This study found that inquiry learning can improve most of the students' motivation and learning outcomes, however, a small number of students did not see any improvement. The conclusion of this study shows that through this inquiry learning can increase student motivation and learning outcomes, however, inquiry learning needs to be improved in terms of its model and how the teacher's creativity in providing the latest innovations so that students are more independent and more active. The limitation of this research is the lack of inquiry learning models owned by educators, therefore researchers hope that future researchers if conducting the same research in order to design an incuri learning model that is more attractive to students.